A Golden Rule of Public Finance or a Fixed Deficit Regime? Growth and Welfare Effects of Budget Rules - Max Groneck (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2008)
In this paper, we compare growth and welfare eects of various budget rules within an endogenous growth model with productive public capital, utility enhancing public consumption and public debt. We find that a fixed deficit regime does not affect the long run growth rate compared to a balanced budget while the growth rate is increased by a golden rule. Welfare effects are ambiguous. Simulations indicate that economies populated by households who have a strong tendency to smooth consumption should adhere to a balanced budget rather than a golden rule or a fixed deficit rule from a welfare point of view.
Keywords: E62; H63; O40; H50; H62; 330; Budget rules; golden rule of public finance; fiscal policy; endogenous growth; welfare; Finanzpolitik; Haushaltsdefizit; Regelgebundene Politik; Wirtschaftspolitische Wirkungsanalyse; Wirtschaftswachstum; Neue Wachstumstheorie; Wohlfahrtseffekt; Theorie